Pengaruh Literasi Keuangan, Inklusi Keuangan, Financial Technology, dan Pengetahuan Akuntansi terhadap Perilaku Keuangan Mahasiswa Akuntansi di Jakarta - Amin Wijoyo; Ferry Adang (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to obtain empirical evidence regarding the influence of financial literacy, financial inclusion, financial technology (fintech), and accounting knowledge on the financial behavior of accounting students in Jakarta. Accounting students were chosen as the research subjects because they have acquired both basic and advanced knowledge of financial management, which is expected to shape more rational and planned financial behavior. This research also seeks to evaluate the extent to which financial literacy, financial inclusion, and the use of modern financial technology contribute to encouraging wiser financial decision-making among students. Data were collected from active accounting students at several universities in Jakarta through online questionnaires. The data were initially processed using Microsoft Excel and further analyzed with the Partial Least Squares (PLS) method to examine the relationships between variables. The results of this study are expected to provide deeper insights into the factors that influence students’ financial behavior and contribute theoretically to the growing body of literature on financial literacy and behavior among educated young adults. Practically, the findings of this study are expected to serve as valuable input for educational institutions in designing more effective financial literacy curricula and activities. Moreover, the results may offer useful recommendations for policymakers and financial industry stakeholders in developing inclusion and education strategies that align with the characteristics of accounting students in Jakarta.